The Role of Human Resource Information System (HRIS) in Improving the Efficiency of the Recruitment Process in the Revolutionary Era 4.0 - Eka Noor Farida; Muhammad Rizal Fauzi; Khuzaini; Syahrial Shaddiq (Jurnal Riset Multidisiplin Edukasi, 2025)
The era of revolution 4.0 is an era of digitalization, automation and centralization. The use of IOT, big data and cloud computing is starting to be implemented in various fields including Human Resource Management. One form of implementation is the use of AI-based HRIS software in the recruitment process. The implementation of HRIS certainly brings various positive impacts on performance efficiency and increased productivity. The purpose of this research is to analyze the efficiency of HRIS in the recruitment process, find out the various AI-based HRIS software and find out the challenges faced. The method used is a literature study by collecting various relevant sources. The results obtained are that HRIS implementation can increase time efficiency, cost efficiency and user satisfaction. Various HRIS features such as Fetcher, XOR, hireEZ, Eightfold, Pymetrics, Textio, Humanly, AllyO, Loxo, Turbohire and SaaS. These features offer various positive impacts on efficiency such as AllyO with 60% cost efficiency and 92% user satisfaction, SaaS with 42% cost efficiency and 46% user satisfaction and humanly being able to shorten candidate screening time by 60 hours. HRIS implementation also faces challenges such as high initial implementation costs, employee resistance and data security.